Arthropod Preference Test Against Zinnia sp. in Oryza Sativa L. - M. Indar Pramudi; Harmi Harmi; Yusriadi Marsuni (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2022)
Arthropoda Preference Test has been carried out on Zinnia Sp. In paddy plantations (Oryza sativa L.). This study aims to determine the level of arthropod diversity in paddy cultivation areas using Zinnia sp. compared to rice without Zinnia sp. The method used is a survey method with purposive sampling which was determined intentionally. The results of the comparison of the 2 treatments showed that in the vegetative phase the number of pests, predators, and parasitoids was more without treatment than using treatment, while the generative phase used less treatment than without treatment. Indeed, from the number of species obtained, there was no signicant difference, but it was seen from the number of fewer pests and more predators with refugia plantations compared to those without refugia. This is evidenced by the comparison of rice yields obtained more with treatment than without treatment 561:429 in units of kg.